Augustine, the Trinity and the Theological Crisis of the West - Gunton, Colin E. (Scottish journal of theology, 1990)
We live in a culture marked, as few others have been, by persistent and deep-seated scepticism about the existence and knowability of God. Not only is the intellectual leadership of our times for the most part atheist or agnostic, but theology itself, certainly since the time of Kant, has been in fundamental disarray about the question, as witness, for example, the recent preoccupation with the question of revelation. In this paper I want to suggest, first, that the problem does not begin with Kant, because at least one of the causes of Western atheism is a theological tradition which encourages thought in the essential unknowability of God. Here, a distinction must be drawn. In one sense, of course, the doctrine of the unknowability of God is essential to theology. But to hold it in such a way as to suggest or teach that the unknowable God can in noway make himself known — so that there can be no theological ontology at all — is to offer the kind of hostages to fortune which so much Western theology has done. Can it really be a historical accident that it is here rather than anywhere else that atheism has found so fertile a soil?